2009
DOI: 10.1002/ijc.24733
|View full text |Cite|
|
Sign up to set email alerts
|

Down regulation of membrane‐bound Neu3 constitutes a new potential marker for childhood acute lymphoblastic leukemia and induces apoptosis suppression of neoplastic cells

Abstract: Membrane-linked sialidase Neu3 is a key enzyme for the extralysosomal catabolism of gangliosides. In this respect, it regulates pivotal cell surface events, including trans-membrane signaling, and plays an essential role in carcinogenesis. In this report, we demonstrated that acute lymphoblastic leukemia (ALL), lymphoblasts (primary cells from patients and cell lines) are characterized by a marked down-regulation of Neu3 in terms of both gene expression (230 to 40%) and enzymatic activity toward ganglioside GD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Moreover, the high expression of Neu5,9Ac 2 -GPs on the lymphoblasts plays a role in their survival [39,40] and that of O-acetylated sialoglycoconjugates in maturation of erythrocytes [41]. These expressions are orchestrated by a series of enzymes [42][43][44][45]. Therefore, modulating one or more of these enzymes and/or targeting them for drugtargeted immunotherapy might be of help in managing this disease.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the high expression of Neu5,9Ac 2 -GPs on the lymphoblasts plays a role in their survival [39,40] and that of O-acetylated sialoglycoconjugates in maturation of erythrocytes [41]. These expressions are orchestrated by a series of enzymes [42][43][44][45]. Therefore, modulating one or more of these enzymes and/or targeting them for drugtargeted immunotherapy might be of help in managing this disease.…”
Section: Discussionmentioning
confidence: 97%
“…Phosphatidyl-serine externalization was analyzed by double staining the cells with FITC-annexin V and PI (5 µg/ml) [38]. Alternatively, treated cells were stained with 7-AAD for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…However some genetic changes altering the expressions of hematopoietic transcription factors are suspected to be responsible for the malignant transformation [164] (for more detailed information about characteristics of ALL, please see reviews [165] and [166]). A recent report showed that membrane-bound sialidase, an enzyme responsible for the degradation of gangliosides, was downregulated in ALL; and when sialidase was overexpressed, apoptotic induction was obtained with the concomitant increase in ceramide levels and decrease in lactosylceramide [167]. By another report, ganglioside GD3 was found to be upregulated [168] and O-acetylated in ALL cells rendering it unable to induce apoptosis suggesting that it is a survival trick adopted by leukemic cells [169].…”
Section: Targeting Sphingolipid Metabolism For the Treatment Of Leukementioning
confidence: 99%